The influence of AI Anxiety and Neuroticism in Attitudes toward Artificial Intelligence - Florin Stănescu, Dan; Constantin Romașcanu, Marius (European Journal of Sustainable Development, 2024)
This paper examines the impact of AI anxiety and neuroticism on attitudes toward Artificial Intelligence (AI) through a quantitative approach. With the pervasive integration of AI technologies across diverse domains like social media platforms, smart devices, healthcare, and education, gaining insight into how individuals perceive and engage with AI becomes essential. A sample of 197 participants (32 males, and 165 females) completed surveys assessing their levels of AI anxiety, neuroticism, and attitudes toward AI. The data were collected via Google Forms using the following structured questionnaires: Artificial Intelligence Anxiety Scale (AIA), Artificial Intelligence Attitude Scale (AIAS-4), and Neuroticism Scale. The findings indicate significant negative correlations between AI anxiety (r=-.286, p<.01), neuroticism (r=-.196, p<.01), and attitudes toward AI, suggesting that individuals with higher levels of AI anxiety and neuroticism are inclined towards adopting more skeptical viewpoints regarding AI technologies. Moreover, the AI anxiety subscales (learning, r=-.152, p<.05; job replacement, r=-.257, p<.01; sociotechnical blindness, r=-.302, p<.01, and AI configuration, r=-.256, p<.01) also showed negative significant correlations with the attitudes toward AI. At the same time, neuroticism showed significant positive correlations with the composite score of AI anxiety (r=.301, p<.01) and all its subscales (learning, r=.219, p<.01; job replacement, r=.250, p<.01; sociotechnical blindness, r=.226, p<.01, and AI configuration, r=.277, p<.01). Understanding the role of AI anxiety and neuroticism in shaping attitudes toward AI can inform the development of strategies to mitigate negative perceptions and foster more positive attitudes toward AI technologies Keywords: artificial intelligence, anxiety, neuroticism, mediation